George Rochberg, American composer : personal trauma and artistic creativity - Wlodarski, Amy Lynn (Eastman studies in music., 2019)
Based on private diaries, correspondence, and unpublished writings, George Rochberg, American Composer reveals the impact of personal trauma on the creative and intellectual work of a leading postmodern composer.